Narrative Psychology and Vygotsky in Dialogue: Changing Subjects - Garraway, James (Critical Studies in Teaching and Learning, 2023)
In  a special  edition  of the journal  ‘Alternations’ (2019) on  the  extended  programmes in universities  in  South  Africa,  authors  highlighted  the  paucity  of theoretical underpinnings  in published  articles  on  teaching  approaches  (these  programmes  are  aimed  at  supporting  non-traditional students’ ability to bridge between school and university). One of the concerns was that although there was much reference to Vygotsky’s work his developmental  theories  were largely underdeveloped. Jill Bradbury’s book Narrative  Psychology  and  Vygotsky  in  Dialogue, though not primarily focused on new students’ learning, may offer readers greater insight into the use of Vygotsky’s principles in student learning. Jill  Bradbury is  a  Professor  of Psychology at  the  University  of  the  Witwatersrand,  South Africa.  Her  teaching  and  research  focus is on  narrative  psychology with  a  particular  focus  on sociohistorical theories of  personhood  development,  educational  transformation and  social change, and the role narrative may play in these. She is the principle investigator in the ‘Narrative Enquiry for Social Transformation’ (NEST) project.